STUDI KASUS : GAMBARAN KARAKTERISTIK PENDERITA PENYAKIT INFEKSI MENULAR SEKSUAL AKIBAT BAKTERI NEISSERIA GONORRHOEAE DI PUSKESMAS MLATI 1 TAHUN 2022 - Mezi Putri Arifani; Nadia Nanda Safitri; Nazula Rahma Shafriani; Diktia Sani Kisna Anita (Akademi Kesehatan John Paul II Pekanbaru, 2023)
Gonorrhea, also known as gonorrhea, is a contagious infectious disease caused by the bacterium Neisseria gonorrhoeae. This disease is transmitted through sexual intercourse and bad habits of changing partners. The symptoms are generally asymptomatic. Purpose: this study aims to discuss the Characteristicsof Sufferers of Sexually Transmitted Infection Disease Due to Neisseria gonorrhoeae bacteria based on age and gender at the Mlati 1 Public Health Center in January-December 2022. Method: the method used is descriptive with a Cross Sectional Study approach.Results: based on the research data conducted, the results of reactive gonorrhea were 21 cases (28%) with the largest population age being adolescents 15-25 years with a total of 11 cases (52.3%). Then, in the adult age group 26-45 years there were 8 (38.2%) cases and the elderly age group 46-65 years with 2 (9.5%) cases. Gonorrhea sufferers were predominantly found in males with a total of 18 cases (85.7%) and in females totaling 3 (14.3%). Conclusion: Overview of STI cases with reactive gonorrhea with a total of 21 cases occurring in the 15-25 year age group of adolescents, and found in males.